Desigualdade de renda no nordeste brasileiro no período recente, 2001-2007 - Santos, Ana Aracelly Lima (2009)
Income inequality is a widely discussed topic in economic theory, however controversial. Nevertheless empirical data have shown significant and continuous declines in Brazilian income inequality in past recent years. The aim of this study is to examine whether Northeast Region income inequality rates follows the same trend observed in national data from 2001 to 2007, examining also the behavior of each state; and which, among the six sources of total income assessed, has contributed the most to results. Thus, it was developed an applied, quantitative and descriptive research, based on bibliographic and empirical sources. It was used the National Household Sample Survey (PNAD) as basis to analyze both household and household per capita income variables. Lorenz curve, Gini index, Theil measures; concentration ratio; and Gini decomposition were used as inequality measures. Results have shown that Brazilian Northeast Region income inequality has reduced and the states of Ceará, Pernambuco and Bahia have positively influenced this decrease. Considering total income sources, government income transfers have strongly contributed to this result. And finally, it was found that Piauí State is the most unequal in the region.